1H NMR combined with PLS for the rapid determination of squalene and sterols in vegetable oils. (30th July 2019) - Shi, Ting; Zhu, MengTing; Zhou, XingYu; Huo, Xi; Long, You; Zeng, XiangZhong; Chen, Yi
Highlights: 1 H NMR and PLS were employed to detect squalene and sterols in vegetable oils. PLS was optimized by outlier removal, input X-variables and data pretreatments. The squalene model was improved by a reduced number of variables with VIP scores. This method showed a rapid determination of squalene and sterols for vegetable oil. Abstract: Proton nuclear magnetic resonance ( 1 H NMR) combined with partial least squares (PLS) was developed for the rapid determination of squalene and sterols (brassicasterol, campesterol, stigmasterol and β-sitosterol) in 119 vegetable oils from 7 different species. The 1 H NMR spectra of these oil samples were correlated to the reference value determined by gas chromatography-mass spectrometry (GC–MS) method by PLS regression, using outlier removal, selection of input X-variables and data pretreatments. Auto-scaling (UV) was chosen as the best pre-processing for the PLS models of stigmasterol, β-sitosterol, and squalene. Pareto variance (Par) was more suitable for the PLS model of brassicasterol. The model for squalene was further improved by a reduced number of variables with variable importance for the projection (VIP) scores technique. The study demonstrated the potential application of NMR coupled with PLS as a rapid and nondestructive technique for the routine analysis of squalene and sterols in vegetable oils.